Composition of Chicken Liver Nugget to Organoleptic and Hemoglobin Levels in the Efforts to Prevent Adolescent Female Anemia - Hamidiyah, Azizatul (International Conference on Sustainable Health Promotion, 2018)
One of the efforts to deal with anemia is through increased consumption of foods that contain lots of iron. The highest iron in animal sources from chicken liver. The purpose of this study was to determine the effect of the composition of chicken liver nugget on Organoleptic and hemoglobin levels in efforts to prevent anemia in the adolescent female. This research was quantitative descriptive research with the pre-experimental design. The sample in the study was 70 teenage female who were 30 respondents as organoleptic respondent and 40 respondents divided into four groups with the intervention of different types of nugget composition. With ten respondents in each group. Data collection was done by measuring preferred consumption from the organoleptic test and the pre and post hemoglobin level consumption of chicken liver nugget. The results of the organoleptic test showed that the majority respondent prefers to consume T2 chicken liver nugget with mean 3.31 which have 20% chicken liver. And the results showed that hemoglobin levels increased after consuming T2 chicken liver nugget by 90% with an average hemoglobin increase of 1.72 gr / dL.